From the original article to the summary for patients: Reformulation procedures in intralingual translation - Muñoz-Miquel, Ana (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The wider access to information and the tendency toward patient education have increased the demand for medical texts aimed at a wide, non-specialized, heterogeneous audience. In this context, it is essential to know what procedures are required to make specialized knowledge accessible to non-experts. This paper presents a corpus-based exploratory study that describes the procedures employed to reformulate, intralingually, medical knowledge from a highly specialized genre, the original article (OA), into a genre derived directly from it but addressed to laymen, namely, the summary for patients (SP). The linguistic and textual changes that take place when translating an OA into an SP are taken as the basis for explaining the reformulation procedures used. The results of the study contribute to the characterization of the SP from a text genre perspective, and provide keys to writing and reformulating for both medical translators and experts in the field, who are often called upon to carry out these intralingual translations.